2013
DOI: 10.1002/hep.26659
|View full text |Cite
|
Sign up to set email alerts
|

Autophagy suppresses tumorigenesis of hepatitis B virus‐associated hepatocellular carcinoma through degradation of microRNA‐224

Abstract: In hepatocellular carcinoma (HCC), dysregulated expression of microRNA-224 (miR-224) and impaired autophagy have been reported separately. However, the relationship between them has not been explored. In this study we determined that autophagy is down-regulated and inversely correlated with miR-224 expression in hepatitis B virus (HBV)-associated HCC patient specimens. These results were confirmed in liver tumors of HBV X gene transgenic mice. Furthermore, miR-224 was preferentially recruited and degraded duri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
152
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 169 publications
(161 citation statements)
references
References 33 publications
2
152
0
Order By: Relevance
“…MiR-224 promotes HCC tumorigenesis through targeting and silencing Smad4 gene. Smad4 contains two miR-224-binding sites in the 3′untranslated region and acts as a tumor suppressor role [21]. It was also reported that miR-224 acts as an oncogenic role in the cellular processes by targeting Smad4 in CRC [22].…”
Section: Mir-224 In Tumorigenesismentioning
confidence: 98%
“…MiR-224 promotes HCC tumorigenesis through targeting and silencing Smad4 gene. Smad4 contains two miR-224-binding sites in the 3′untranslated region and acts as a tumor suppressor role [21]. It was also reported that miR-224 acts as an oncogenic role in the cellular processes by targeting Smad4 in CRC [22].…”
Section: Mir-224 In Tumorigenesismentioning
confidence: 98%
“…Previous studies have shown that the canonical autophagy machinery can function in antibacterial and antiviral host defense by delivering intracellular pathogens or components of intracellular pathogens to the lysosome for degradation (2,36). Moreover, Beclin 1 and the autophagy pathway has been proposed to function in controlling viral oncogenesis in at least two contexts: monoallelic deletion of Becn1 accelerates neoplastic lesions in the livers of mice that transgenically express hepatitis B envelope protein autophagy (30) and decreased autophagic degradation of a microRNA (miR-224) is postulated to contribute to hepatitis B virus-associated hepatocellular carcinoma in mice and in humans (42). Our findings suggest that independently of the autophagy machinery, the delivery of viral oncoproteins to the lysosome for degradation (via an endolysosomal trafficking route) may play a crucial role in innate immunity.…”
Section: Discussionmentioning
confidence: 99%
“…(Lan et al, 2014a) Autophagy specifically has been shown to suppress HBV-associated tumor formation by degrading microRNA-224. (Lan et al, 2014b)…”
Section: Autophagic Membranes In Classical Viral Envelope Formationmentioning
confidence: 99%